The Correlation Between Interpersonal Intelligence and the English-Speaking Ability of Students Pharmacy Department at SMK Yadika Palu - Yulianisa; Dzakiah; Kuliahana, Ana (UNESA, 2025)
This research aims to determine whether there is a significant correlation between interpersonal intelligence and English language skills of students of the Pharmacy Department of SMK Yadika Palu. The approach used was quantitative with a correlation method, involving a sample of 30 class XI Pharmacy students selected by purposive sampling. The instruments used in this research consisted of a questionnaire to measure students' interpersonal intelligence and a speaking test to assess English speaking ability. The data were analysed through several stages, including the normality test and Pearson Product-Moment correlation test processed using SPSS version 26 for Windows. The results of the normality test showed that the data were normally distributed, and the Pearson correlation test showed a significant and positive correlation between interpersonal intelligence and English-speaking ability, with a correlation coefficient of 0.776 and a significance value of 0.000 (p < 0.05). This correlation is categorised as a high correlation. In addition, 60.3% of the variance in English-speaking ability can be explained by the interpersonal intelligence variable. These findings indicate that the higher the level of interpersonal intelligence possessed by students, the better their English speaking ability.